Perception of Social Studies' teachers on socio-economic integration in selected African countries. (2nd January 2017) - Otunla, Julius Aderemi; Oyelana, Akeem Adewale; Adelabu, Olusesan Adeyemi
ABSTRACT: Economic and social integration has been said to be the hallmark of good governance. This research aimed at assessing the awareness of Social Studies' teachers in South-West Nigeria about the effects of economic and social integration in the region. Data were collected through self-administered questionnaires through the use of random sampling. The objectives of the research were to examine the perception and also to assess the awareness of Social Studies' teachers on the economic and social integration in South-West Nigeria. Data analysis was conducted using descriptive statistics. The field survey confirmed that some of these barriers were notably political in nature. They include: cultural values, religion and beliefs, needs, social themes and economy. The findings also identified the search for solutions to these barriers faced by the people in South-West Nigeria by providing an insight for further research regarding the institutional weaknesses and policy issues in this part of the world. The implications of the findings were that unless the limitations named above are resolved, the economic and social integration in the South-West Nigeria will continue to experience poor economic growth and development. Recommendations to overcome these barriers are suggested.